MEMORANDUM TO EXECUTIVE COMMITTEE CONCERNING ETS - CHILCOTE,SAMUEL D JR (Tufts Archival Research Center, 2007)
Handwritten; Memorandum from Sam Chilcote to the Executive Committee of the Tobacco Institute outlining new strategies to counter the growing concern over environmental tobacco smoke (ETS). Reports that strategy to broaden the issue of ETS to include indoor air quality (IAQ) has been successful. Includes updates on media and scientific projects regarding ETS and IAQ and a list of strategies for future action.